2020
DOI: 10.21203/rs.2.24566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic evidence for imported malaria and local transmission in Richard Toll, Senegal

Abstract: Background: Malaria elimination efforts can be undermined by imported malaria infections. Imported infections are classified based on travel history.Methods: We applied a genetic strategy to better understand the contribution of imported infections and to test for local transmission in the very low prevalence region of Richard Toll, Senegal.Results: Genetic relatedness analysis, based upon molecular barcode genotyping data derived from diagnostic material, provided evidence for both imported infections and ong… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Malaria parasite molecular data have been utilized for a wide set of research and programmatic questions beyond drug and diagnostic resistance detection. Molecular data enables the identification of different malaria species [9, 10] providing especially helpful information in regions where malaria infections were either absent or considered completely imported [11]. An extensive library of parasite genetic samples can also help researchers and programmatic investigators during an out-break to help determine the geographic origin, rate of importation, and subsequent level of local transmission [12, 13, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria parasite molecular data have been utilized for a wide set of research and programmatic questions beyond drug and diagnostic resistance detection. Molecular data enables the identification of different malaria species [9, 10] providing especially helpful information in regions where malaria infections were either absent or considered completely imported [11]. An extensive library of parasite genetic samples can also help researchers and programmatic investigators during an out-break to help determine the geographic origin, rate of importation, and subsequent level of local transmission [12, 13, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular data enables the identification of different malaria species [9, 10] providing especially helpful information in regions where malaria infections were either absent or considered completely imported [11]. An extensive library of parasite genetic samples can also help researchers and programmatic investigators during an out-break to help determine the geographic origin, rate of importation, and subsequent level of local transmission [12, 13, 11]. More broadly, genetic similarity between samples has been used to identify the parasite connectivity between human populations [14, 15, 16, 17, 18, 19], which may provide a pragmatic and cost-effective tool to inform control programs as they plan local elimination efforts [20].…”
Section: Introductionmentioning
confidence: 99%
“…Unscheduled visits in which study subjects had Re-infected participants were all from the same household (MS). Parasite genotypes from the first infection were genetically distinct from the re-infected parasites ( Figure 4), and three of them (U5, U6 and U7) represented genotypes which had not been previously described, either in Thiès or in multiple regions of Senegal from 2006-present 14,16,21 .…”
Section: Genomic Signatures Among Initial and Re-infectionmentioning
confidence: 73%
“…Having such different parasites in the same household could be the result of a hotspot of local intense transmission 17 , coupled with genetic recombination (outcrossing) within the Anopheles mosquito 26 , and the subsequent transmission of new genetic combinations 17 . An alternative could be the importation of diverse genotypes due to human or mosquito mobility 21,[27][28][29][30] . A similar study of malaria incidence and prevalence has demonstrated the existence of malaria transmission hotspots at the village level in Senegal 7,8 .…”
Section: Discussionmentioning
confidence: 99%